Current status and influencing factors of care burden of pancreatic cancer caregivers under COVID-19 - Sun, Qingmei; Li, Jiarong; Fang, Xiaoping; Jin, Jie; Cui, Lei (Frontiers in Psychology, 2023)
[Objective] To explore the level of care burden and its influencing factors of caregivers of pancreatic cancer patients during hospitalization under the background of COVID-19. [Methods] From September 2021 to December 2021, in Jiangsu Province Hospital, the convenience sampling method was used to investigate the care burden level of family caregivers of pancreatic cancer patients, and univariate and multivariate analysis methods were used to analyze the influencing factors. The survey tools included the General Information Questionnaire, the Family Caregiver Care Burden Scale, the Hospital Anxiety and Depression Scale, the Benefit Discovery Rating Scale, and the General Self-Efficacy Scale. [Results] A total of 100 subjects were included in this study, of which 45% were male and 55% were older than 50 years. In the Context of COVID-19, the care burden of caregivers of pancreatic cancer patients was at a mild level, and the main influencing factors were family economic status (P < 0.001), anxiety and depression level (P < 0.001) and self-efficacy (P < 0.001). [Conclusion] Medical staff should pay attention to the caregivers of pancreatic cancer with a heavy family burden, and pay attention to their anxiety and depression, and take corresponding measures to improve the self-efficacy of the caregivers, so as to reduce the care burden.